Rare and de novo duplications containing TCF20 are associated with a neurodevelopmental disorder. Issue 3 (28th December 2021) - Lévy, Jonathan; Cogan, Guillaume; Maruani, Anna; Maillard, Arnaud; Dupont, Céline; Drunat, Séverine; Rachid, Myriam; Atzori, Paola; Delorme, Richard; Jeyarajah, Sabatini; Isidor, Bertrand; Pichon, Olivier; et al.
Abstract: Transcriptor co‐activator factor 20 gene ( TCF20 ) encodes a nuclear chromatin‐binding protein involved in regulation of gene expression. In human pathology, pathogenic variants or deletions in TCF20 were identified in patients with developmental delay, variable intellectual disability and behavioral impairment (OMIM: 618430). The shared core phenotype includes developmental delay, hypotonia, motor delay, autism spectrum disorders, neurobehavioral anomalies, neurological features such as ataxia, seizures, movement disorders, structural brain anomalies, craniofacial features and various congenital anomalies. Most pathogenic variants are loss‐of‐function variants. Duplication including TCF20 was suspected to cause a neurodevelopmental disorder (NDD) with mirror traits compared to patients with TCF20 deletions. In the present study, we report three patients from three unrelated families with NDD with a de novo duplication at 22q13.2 encompassing TCF20 . We propose that the TCF20 duplication could be involved in a new 22q13.2 microduplication syndrome with high penetrance, enlarging the genotype–phenotype knowledge of TCF20‐ associated NDDs. Abstract : We report three patients with a de novo 22q13.2 microduplication covering the TCF20 gene associated with syndromic neurodevelopmental disorder including developmental delay/intellectual disability, speech delay, neuropsychiatric features, nonspecific dysmorphic facial features, structural brain ophthalmologic and/or skeletal anomalies.